THE DETERMINANTS OF ECONOMIC FREEDOM: A SURVEY. (11th March 2020) - Lawson, Robert A.; Murphy, Ryan; Powell, Benjamin
Abstract : A large literature has found positive associations between economic freedom and income, growth, and a variety of other desirable outcomes. This paper surveys the literature that seeks to explain the causes of economic freedom. Some of the most consistent findings in this literature are that current levels of economic freedom are strongly correlated with past levels; freer countries have more difficulty continuing to improve their economic freedom; democracy and political freedom are positively associated with economic freedom; and inequality is negatively related. ( JEL E02, E14, O17, O43, P1)